2019
DOI: 10.11606/s1518-8787.2018052000616
|View full text |Cite
|
Sign up to set email alerts
|

Frailty profile in Brazilian older adults

Abstract: OBJECTIVE To estimate the prevalence of frailty and to evaluate the associated factors in the non-institutionalized Brazilian population aged 50 years or older.METHODS The analyses were conducted in 8,556 participants of the baseline survey of the Longitudinal Study of Health of the Brazilian Elderly (ELSI-Brazil) conducted in 2015 and 2016. Frailty was defined based on five characteristics: weight loss, weakness, slowness, exhaustion and low level of physical activity. Participants with three or more characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
3
30

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 25 publications
6
66
3
30
Order By: Relevance
“…The importance of partner support in relation to frailty, emphasizes the need for social support [21]. Persons with lower education and lower income may access health services and practice health behaviors less often, which may contribute to the development of frailty [10,21]. Compared to Sumatra, the prevalence of frailty was higher in the other study regions (Java, Major island groups).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The importance of partner support in relation to frailty, emphasizes the need for social support [21]. Persons with lower education and lower income may access health services and practice health behaviors less often, which may contribute to the development of frailty [10,21]. Compared to Sumatra, the prevalence of frailty was higher in the other study regions (Java, Major island groups).…”
Section: Discussionmentioning
confidence: 92%
“…In consistence with previous studies [9,[12][13][14][15], this study found that older age, being unmarried, separated, divorced or widowed, and in the bivariate analysis that poorer economic status and lower education were associated with frailty. Frailty is associated with aging by accumulating deficiencies in several physiological systems [21]. The importance of partner support in relation to frailty, emphasizes the need for social support [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations